Results of posterior and posterolateral decompressive approaches in thoraco-lumbar spine traumatic injures - Slihnko, E. I.; Leontiyev, A. Yu.; Panferov, S. A. (Ukrainian Neurosurgical Journal, 2007)
The retrospective analysis of medical records of 91 patients with traumatic thoracolumbar spine injury, whom operative decompression from posterior and posterolateral approaches was performed is done. The neurological status and neurological deficiency were identified according to Frankel scale, Denis and AO/ASIF classification fractures, methods of decompression and fixations were estimated. Indications for application of decompression-stabilization operations through posterior and lateroposterior approaches were the next: heavy and heaviest state of the injured person at spinal cord compression, spinal cord cross-section injury and at compression substratum localization behind and by side the spinal cord. For nervous structures decompression we applied: anulotaxis, laminectomy, facetectomy, corporectomy, hematomas and traumatic hydromas removal, and their combinations. The decompression stage should be finished by injured spine segment fixation in position of deformation correction. After the operation improvement of bladder and bowel functions was achieved at the majority of patients. Neurological deficit significantly regressed.